Gianni Rodari: un aedo del Novecento - Arsena, Angela (Studi sulla Formazione/Open Journal of Education, 2021)
We propose an analysis of the poetics of Gianni Rodari's fables. It focuses on the original problem of human storytelling, that is, on the possibility of finding the origin or the primordial topic of the narrative fact: the problem of the beginning, the bevor, the "absolute first", addresses, or tries to address the issue of the meaning, of the deep significance of storytelling. Integrated in the thousand-year old tradition of human storytelling experience, Gianni Rodari shows how the language of a fable springs out of the extraordinary experience of the wide-eyed gaze of a children upon the world.